Short-Term Regional Demographic Forecasts with Time Series Methods and Machine Learning Algorithms - Bravo, Jorge Miguel (2021)
Bravo, J. M., & Coelho, E. (2020). Short-Term Regional Demographic Forecasts with Time Series Methods and Machine Learning Algorithms. Boletim da Sociedade Portuguesa de Estatística, (Primavera 2020), 20-29.